SCoTCH-seq reveals that 5-hydroxymethylcytosine encodes regulatory information across DNA strands - Jack S. Hardwick; Somdutta Dhir; Angie Kirchner; Angela Simeone; Sean M. Flynn; James M. Edgerton; Rafael de Cesaris Araujo Tavares; Isabel Esain-Garcia; David Tannahill; Paula Golder; Jack M. Monahan; Walraj S. Gosal; et al. (Proceedings of the National Academy of Sciences, 2025)
In mammalian genomes, cytosine modifications form a layer of regulatory information alongside the genetic code. Decoding this information is crucial to our understanding of biology and disease. Established sequencing methods cannot simultaneously resolve cytosine’s three most common forms—cytosine (C), 5-methylcytosine (mC), and 5-hydroxymethylcytosine (hmC)—across both strands of the DNA double helix. Thus, how epigenetic information is distributed in DNA remains unclear. Here, we present S trand- Co upled T andem C ytosine H ydroxymethylation and methylation sequencing (SCoTCH-seq): an accurate and quantitative, base-resolution approach to sequence genomes, together with mC and hmC, in both strands of the same DNA fragment. We show that different forms of cytosine combine across the double helix at CpG sites to form discrete information states in the mouse epigenome. These CpG states have distinct genomic distributions—including at promoters, enhancers, and gene bodies—and have different relationships with transcription. We show that while all possible forms of hydroxymethylation occur, hmC is predominantly asymmetric and that different forms of asymmetric hmC are not equivalent. Our findings demonstrate that 5-hydroxymethylcytosine combines with different cytosine variants across the DNA double helix to form distinct states of regulatory information.